Community Participation in Efforts to Develop Islamic Religious Education - Munir, Miftakhul (Letiges, 2021)
Community participation means that the community participates in and accompanies the government because in reality the government is currently the designer and organizer. Development of Islamic Religious Education (PAI), which means a process or system of hard work to change conditions that are related to the work or products of humans in building Islamic Education to be better in all its aspects and to have a wider impact and benefits than before. The purpose of this study is to describe community participation in efforts to develop Islamic Religious Education (PAI) and supporting and inhibiting factors for community participation in efforts to develop Islamic Religious Education (PAI) in Karangketug Village, Gadingrejo District, Pasuruan City. This research is a qualitative research approach. The informants of this research were the head of RW 3, the head of the RT and the surrounding community. Data collection methods in this study are observation, interviews and documentation. Sources of data used in this study are primary data sources and secondary data sources. The results obtained from this study are 1) Community participation in efforts to develop Islamic Religious Education (PAI) in Karangketug Village, Gadingrejo District, Pasuruan City can be seen in terms of: first, community participation in developing various religious activities. Second, participation in providing support with religious activities. Third, participation in funding and infrastructure for Islamic Religious Education, namely by making contributions that have been mutually agreed upon and contributing to Islamic religious education infrastructure, namely in the form of equipment for samroh activities such as tambourines and so on. 2) The supporting factors for community participation in efforts to develop Islamic Religious Education (PAI) are the support from various parties including the village government, the head of RW 3, the head of RT 1, and the surrounding community. The inhibiting factors for community participation in efforts to develop Islamic Religious Education (PAI) are erratic community time together, weather, health conditions, and a small proportion of people who are lazy to participate in activities.